Novel dihydroartemisinin derivative DHA-37 induces autophagic cell death through upregulation of HMGB1 in A549 cells. Issue 11 (November 2018) - Liu, Xiufeng; Wu, Juanjuan; Fan, Menglin; Shen, Chen; Dai, Wenling; Bao, Yini; Liu, Ji-Hua; Yu, Bo-Yang
Abstract Dihydroartemisinin (DHA) and its analogs are reported to possess selective anticancer activity. Here, we reported a novel DHA derivative DHA-37 that exhibited more potent anticancer activity on the cells tested. Distinct from DHA-induced apoptosis, DHA-37 triggered excessive autophagic cell death, and became the main contributor to DHA-37-induced A549 cell death. Incubation of the cells with DHA-37 but not DHA produced increased dots distribution of GFP-LC3 and expression ratio of LC3-II/LC3-I, and enhanced the formation of autophagic vacuoles as revealed by TEM. Treatment with the autophagy inhibitor 3-MA, LY294002, or chloroquine could reverse DHA-37-induced cell death. In addition, DHA-37-induced cell death was associated significantly with the increased expression of HMGB1, and knockdown of HMGB1 could reverse DHA-37-induced cell death. More importantly, the elevated HMGB1 expression induced autophagy through the activation of the MAPK signal but not PI3K-AKT–mTOR pathway. In addition, DHA-37 also showed a wonderful performance in A549 xenograft mice model. These findings suggest that HMGB1 as a target candidate for apoptosis-resistant cancer treatment and artemisinin-based drugs could be used in inducing autophagic cell death.